Prevalence of vitamin B12 deficiency in type 2 diabetic patients using metformin: a cross-sectional study - Damião, Charbel Pereira (2016)
CONTEXT AND OBJECTIVE: The prevalence of vitamin B12 deficiency varies from 5.8% to 30% among patients undergoing long-term treatment with metformin. Because of the paucity of data on Brazilian patients, this study aimed to determine the frequency of B12 deficiency and related factors among Brazilian patients with type 2 diabetes mellitus (T2DM) using metformin. DESIGN AND SETTING: Cross-sectional study at a public university hospital. METHODS: Patients with T2DM and a control group of non-diabetics were included. Serum B12 levels were measured and biochemical B12 deficiency was defined as serum levels < 180 pg/ml. Associations between B12 deficiency and age, duration of T2DM, duration of use and dosage of metformin, and use of proton pump inhibitors (PPIs) or histamine H2 antagonists were determined. RESULTS: 231 T2DM patients using metformin (T2DM-met) and 231 controls were included. No difference in the frequency of PPI or H2-antagonist use was seen between the groups. B12 deficiency was more frequent in the T2DM-met group (22.5% versus 7.4%) and this difference persisted after excluding PPI/ H2-antagonist users (17.9% versus 5.6%). The factors that interfered with serum B12 levels were PPI/H2- antagonist use and duration of metformin use ≥ 10 years. Use of PPI/H2-antagonists was associated with B12 deficiency, with an odds ratio of 2.60 (95% confidence interval, 1.34-5.04). CONCLUSIONS: Among T2DM patients, treatment with metformin and concomitant use of PPI/H2-antagonists are associated with a higher chance of developing B12 deficiency than among non-diabetics.